Chromosomal analysis in IVF: just how useful is it? - Griffin, Darren K.; Ogur, Cagri (BIOSCIENTIFICA LTD, 2018)
Designed to minimize chances of transferring genetically abnormal embryos, preimplantation genetic diagnosis (PGD) involves in vitro fertilization (IVF), embryo biopsy, diagnosis and selective embryo transfer. Preimplantation genetic testing for aneuploidy (PGT-A) aims to avoid miscarriage and live born trisomic offspring and to improve IVF success. Diagnostic approaches include fluorescence in situ hybridization (FISH) and more contemporary comprehensive chromosome screening (CCS) including array comparative genomic hybridization (aCGH), quantitative polymerase chain reaction (PCR), next-generation sequencing (NGS) and karyomapping. NGS has an improved dynamic range, and karyomapping can detect chromosomal and monogenic disorders simultaneously. Mosaicism (commonplace in human embryos) can arise by several mechanisms; those arising initially meiotically (but with a subsequent post-zygotic 'trisomy rescue' event) usually lead to adverse outcomes, whereas the extent to which mosaics that are initially chromosomally normal (but then arise purely post-zygotically) can lead to unaffected live births is uncertain. Polar body (PB) biopsy is the least common sampling method, having drawbacks including cost and inability to detect any paternal contribution. Historically, cleavage-stage (blastomere) biopsy has been the most popular; however, higher abnormality levels, mosaicism and potential for embryo damage have led to it being superseded by blastocyst (trophectoderm-TE) biopsy, which provides more cells for analysis. Improved biopsy, diagnosis and freeze-all strategies collectively have the potential to revolutionize PGT-A, and there is increasing evidence of their combined efficacy. Nonetheless, PGT-A continues to attract criticism, prompting questions of when we consider the evidence base sufficient to justify routine PGT-A? Basic biological research is essential to address unanswered questions concerning the chromosome complement of human embryos, and we thus entreat companies, governments and charities to fund more. This will benefit both IVF patients and prospective parents at risk of aneuploid offspring following natural conception. The aim of this review is to appraise the 'state of the art' in terms of PGT-A, including the controversial areas, and to suggest a practical 'way forward' in terms of future diagnosis and applied research.
Keywords: COMPARATIVE GENOMIC HYBRIDIZATION; PREIMPLANTATION GENETIC DIAGNOSIS; IN-VITRO FERTILIZATION; ADVANCED MATERNAL AGE; RANDOMIZED CONTROLLED-TRIAL; FLUORESCENT INSITU HYBRIDIZATION; EMBRYO CULTURE-MEDIUM; AMINO-ACID TURNOVER; INNER CELL MASS; MOLECULAR CYTOGENETIC ANALYSIS; Developmental Biology; Reproductive Biology